Quizalize App: Teaching English Vocabulary for Young Learners - Ayuningtyas, Olanita; Suwartono, Suwartono; Rinjani, Rinjani (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2025)
Quizalize has been developed as a technological tool to enhance the efficiency of foreign language learning. This study investigates and compares vocabulary recognition outcomes between traditional and Quizalize-based learning methods. Utilizing a quasi-experimental design, the study assessed degrees of freedom (df) as N-1 = 26-1 = 25, with a t-table value of 0.396. The obtained t-value of 0.001 was significantly lower than the t-table value of 0.396. Consequently, the alternative hypothesis (Ha) was supported, and the null hypothesis (Ho) was rejected. These results indicate that Quizalize significantly improves students’ vocabulary recognition. The findings underscore the effectiveness of integrating Quizalize, highlighting its potential to enhance students’ vocabulary acquisition and engagement through interactive and appealing exercises.